Bird and bat predation services in tropical forests and agroforestry landscapes. (23rd July 2015) - Maas, Bea; Karp, Daniel S.; Bumrungsri, Sara; Darras, Kevin; Gonthier, David; Huang, Joe C.‐C.; Lindell, Catherine A.; Maine, Josiah J.; Mestre, Laia; Michel, Nicole L.; Morrison, Emily B.; Perfecto, Ivette; et al.
ABSTRACT: Understanding distribution patterns and multitrophic interactions is critical for managing bat‐ and bird‐mediated ecosystem services such as the suppression of pest and non‐pest arthropods. Despite the ecological and economic importance of bats and birds in tropical forests, agroforestry systems, and agricultural systems mixed with natural forest, a systematic review of their impact is still missing. A growing number of bird and bat exclosure experiments has improved our knowledge allowing new conclusions regarding their roles in food webs and associated ecosystem services. Here, we review the distribution patterns of insectivorous birds and bats, their local and landscape drivers, and their effects on trophic cascades in tropical ecosystems. We report that for birds but not bats community composition and relative importance of functional groups changes conspicuously from forests to habitats including both agricultural areas and forests, here termed 'forest‐agri' habitats, with reduced representation of insectivores in the latter. In contrast to previous theory regarding trophic cascade strength, we find that birds and bats reduce the density and biomass of arthropods in the tropics with effect sizes similar to those in temperate and boreal communities. The relative importance of birds versus bats in regulating pest abundances varies with season, geography and management. Birds and bats may even suppress tropical arthropod outbreaks, although positive effects on plant growth are not always reported. As both bats and birds are major agents of pest suppression, a better understanding of the local and landscape factors driving the variability of their impact is needed.